Evaluasi Tingkat Pelayanan Simpang Tiga Tak Bersinyal pada Simpang Pendem (Jl. Raya Dadaprejo – Jl. Dr. Moh. Hatta – Jl. Ir. Soekarno) Kota Batu - Gire , Sartini; Pandulu, Galih Damar ; Arifianto , Andy Kristafi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Jl. Dadaprejo ? Jl. Ir. Soekarno ? Jl. Dr. Moh. Hatta, who is the area of Batu City Pendem, is one of the intersections that has a high volume of traffic because the intersection is a path leading to tourist attractions and also to several cities. The problem that occurs at the Pendem intersection is the absence of a vehicle controller resulting in traffic congestion and frequent accidents. To overcome the traffic conflict at the Pendem intersection, a development of supporting facilities and anfrastructure is needed, aspecially on improving road networks, crossing planning. Traffic volume data is taken for 14 days (2 weeks) which can the be explored traffic volume desity at rush hour even on weekends. The purpose of this study is to evaluate the performance of existing intersections and analyze alternative solutions to problems that occur at the Pendem intersection.